DAMPAK DESA WISATA DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT LOKAL MELALUI COMMUNITY BASED TOURISM DI DESA CIBURIAL KECAMATAN CIMEUNYAN KABUPATEN BANDUNG - Esa Candra Nugraha; Amida Hanna (PT. Saha Kreasi Indonesia, 2025)
This research analyzes the impact of a tourism village and the implementation of Community Based Tourism (CBT) in Ciburial Village, Cimenyan District, Bandung Regency. This area is rich in natural and cultural potential, with local initiatives such as honey cultivation, agrotourism, Lembur Kaulinan (traditional play area), and local MSMEs (Micro, Small, and Medium Enterprises). The study results show that CBT significantly improves the economic well-being of the community by creating jobs and diversifying livelihoods, with the Pokdarwis (Tourism Awareness Group) serving as the main driver of grassroots initiatives. However, the main challenges lie in the uneven local human resource capacity, reflected in complaints about the lack of specific training in digital marketing, hospitality, and management, which indicates minimal structured assistance from external parties. This is compounded by uneven socialization and a lack of integrated coordination among tourism stakeholders. In addition, basic infrastructure such as road access, clean water, and electricity still needs improvement, and the threat of climate change is a critical factor affecting sustainability. Therefore, this research recommends increasing local human resource capacity through continuous mentoring, strengthening the Village Government's coordination based on empowerment strategies (group formation, functional assistance, activity planning), collaborating with educational institutions (such as SMA Plus Babussalam for a tourism major), and innovating with digital marketing and infrastructure improvements to achieve sustainable and equitable tourism village development.